1989
DOI: 10.1144/gsl.sp.1989.041.01.22
|View full text |Cite
|
Sign up to set email alerts
|

Fan-delta-lacustrine sedimentation and coal development in the Tertiary Ombilin Basin, W Sumatra, Indonesia

Abstract: Summary The Ombilin Basin is a Tertiary intermontane basin situated in the Barisan mountain range of W Sumatra. It covers an area of some 1500 km 2 and is known for the coal resources which have been mined in the Sawahlunto area since 1891. Seismic and borehole data indicate that the basin has been filled with approximately 4600m of middle Eocene to early Miocene sediments. The coal developed early in the basin’s history (middle Eocene). During this study the fan-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Extensive Oligocene coals are known only from the Sawahlunto formation (Ombilin basin), where they form part of the initial rift infill sequence (Koesoemadinata and Matasak, 1981) and from the Pematang formation of Jambi province. The Sawahlunto coal grades laterally into lake deposits (Wateley and Jordan, 1989), and is also rich in algal remains, such as Pediastrum spp. Therefore, the Sawahlunto coal most likely formed from a rheotropic, eutrophic peat.…”
Section: Oligocenementioning
confidence: 99%
“…Extensive Oligocene coals are known only from the Sawahlunto formation (Ombilin basin), where they form part of the initial rift infill sequence (Koesoemadinata and Matasak, 1981) and from the Pematang formation of Jambi province. The Sawahlunto coal grades laterally into lake deposits (Wateley and Jordan, 1989), and is also rich in algal remains, such as Pediastrum spp. Therefore, the Sawahlunto coal most likely formed from a rheotropic, eutrophic peat.…”
Section: Oligocenementioning
confidence: 99%
“…The basin's Cenozoic fill overlies pre-Cenozoic basement rocks and includes in ascending order; the Brani Formation, the Sangkarewang Formation, the Sawahlunto Formation, the Sawahtambang Formation, and the Ombilin Formation (Fatimah and Ward, 2009;Koesoemadinata and Matasak, 1981;Whateley and Jordan, 1989). This study focuses on a small part of the late Paleogene Sawahlunto Formation.…”
Section: Stratigraphic Settingmentioning
confidence: 99%
“…This study focuses on a small part of the late Paleogene Sawahlunto Formation. The oldest sediment in the Ombilin Basin, the Brani Formation, represents Eocene marginal fan deposition and consists of a sequence of breccias and polymictic pebble to cobble conglomerate in a muddy to sandy matrix that interfinger laterally and basinward with the Sangkarewang Formation (Fatimah and Ward, 2009;Whateley and Jordan, 1989). The Sangkarewang Formation is composed of dark bluish gray to black laminated shale that is commonly intercalated with greenish-gray feldspathic turbidite sandstone.…”
Section: Stratigraphic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…1) a small intermontane basin on the western margin of the island of Sumatra. Previous studies have indicated that subsidence of the Ombilin Basin was initiated as early as the Paleocene and was dominated by continental deposition from the basin's origin through the Paleocene, Eocene and Oligocene (Koesoemadinata and Matasak, 1981;Whateley and Jordon, 1989;Fatimah and Ward, 2009). Marine influences are not inferred to have occurred until the Early Miocene, with deposition of fossiliferous limestone and calcareous shale beds of the Ombilin Formation.…”
Section: Introductionmentioning
confidence: 99%